Moments of basic radial and angular forces gap seal of centrifugal pump - Gorovoy, S (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes)
In slotted seals of centrifugal pumps, due to eccentric displacement and angular rotation (skew) of the rotor, deformation of the pressure distribution diagram along the length and perimeter of the seal arises, which gives rise to the resultant main components of the hydrodynamic force: elastic, damping and circulating. The resultant main forces can be transferred to the geometric center of compaction with the formation of the corresponding hydrodynamic moments. These hydrodynamic moments of radial and angular hydrodynamic forces in the slit seal of a centrifugal pump have a significant effect on the dynamic characteristics of the unit in the case when the pump rotor makes coupled radial-angular oscillations. Angular moments are functions of the angles of rotation (skew) of the rotor in the seal. The moment of elastic force creates the angular instability of the rotor in a single seal, but in the presence of two symmetrical gap seals, this moment is compensated by the moments of the resultant elastic forces relative to the geometric center of the entire rotor.